2 - Militancy in the Niger Delta and the Deepening Crisis of the Oil Economy in Nigeria - Uwasomba, Chijioke; Alumona, Victor S. (Africa Development, 2021)
The area known as the Niger Delta spans over 70,000 square kilometers. At the geographical and ecological levels, it is regarded as one of the foremost wetlands in the world, and rated as the ninth vastest drainage area in the world. In 1957, when oil was discovered at Oloibiri in today’s Balyelsa State of Nigeria, the British enacted the Mineral Ordinance Act which vested all the minerals in Nigeria in the British Crown. This Act paved the way for the continued denial that has characterized the relationship between the oil-bearing communities and the central government of Nigeria, leading to the Resource Control agitation by the peoples of the Niger Delta. This article argues that the Nigerian state, true to its colonial origins tightened its grip on the instruments with which to allocate profitable opportunities in the burgeoning oil economy of Nigeria at the expense of the oil-bearing communities. This condition has led to complaints, agitations, and finally to militancy which is crippling the Nigerian economy. The article notes that the Nigerian state and elite forces within and outside the Niger Delta should be held responsible for the crises in the region and concludes that militancy is a product of frustration.